2019
DOI: 10.2214/ajr.18.20036
|View full text |Cite
|
Sign up to set email alerts
|

Multireader Determination of Clinically Significant Obstruction Using Hyperpolarized 129Xe–Ventilation MRI

Abstract: Objective: To identify the magnitude and distribution of ventilation defect score derived from hyperpolarized (HP) 129 Xe magnetic resonance imaging (MRI) associated with clinically relevant airway obstruction. Material and Methods:Our retrospective, HIPAA compliant study was approved by our IRB with written informed consent. From 2012 to 2015, 76 subjects underwent HP 129 Xe MRI (healthy volunteers, n=48 [mean age 54 ± 17 years]; asthma patients, n=20 [mean age 44 ± 20 years]; COPD patients, n=8 [mean age 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…129 Xe ventilation imaging is extremely sensitive to obstructive lung disease, 2 exhibiting increased ventilation heterogeneity and VDP in patients with chronic obstructive lung disease (COPD) [157] , [159] , asthma [155] , [163] , [164] , [311] , cystic fibrosis (CF) [156] , [165] , [166] , [167] and non-small-cell lung cancer [157] , compared to healthy volunteers ( Fig. 2 ).…”
Section: Ventilation Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…129 Xe ventilation imaging is extremely sensitive to obstructive lung disease, 2 exhibiting increased ventilation heterogeneity and VDP in patients with chronic obstructive lung disease (COPD) [157] , [159] , asthma [155] , [163] , [164] , [311] , cystic fibrosis (CF) [156] , [165] , [166] , [167] and non-small-cell lung cancer [157] , compared to healthy volunteers ( Fig. 2 ).…”
Section: Ventilation Imagingmentioning
confidence: 99%
“…A thermally polarised xenon torso phantom for quality assurance has been developed and tested at eight sites across North America [299] . Different approaches to image segmentation for ventilated volumes have been compared [152] , [154] , and substantial inter-reader agreement reported between blinded radiologists [164] . A recent retrospective study of ventilation images acquired at two institutions in children with CF found similar ventilation metrics between sites and strong agreement between two analysts, concluding that multi-centre trials in CF appear to be feasible [166] .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Ventilation imaging using HP 129 Xe has shown sensitivity to early lung function decline and disease progression in a wide variety of pulmonary diseases including asthma, COPD, LAM, and CF. 14,21,31,[51][52][53] Moreover, it has been implemented using both 3 He and 129 Xe in multi-site trials, 54,55 with notable HP 129 Xe multisite studies that included evaluation of CF 16 and asthma patients, 22 as well as recent phase III clinical trials of patients being evaluated for resection and transplant. 41,42 Most notably, ventilation imaging will be the initial indication to be approved by the FDA in the United States and also represents the driver for more than half of referrals received in the clinical setting in the UK to date.…”
Section: Ventilationmentioning
confidence: 99%
“…In Equation (), VV is the lung ventilated volume, and total lung volume ( TLV ) is calculated by segmentation of the thoracic cavity. Ventilation imaging using HP 129 Xe has shown sensitivity to early lung function decline and disease progression in a wide variety of pulmonary diseases including asthma, COPD, LAM, and CF 14,21,31,51‐53 . Moreover, it has been implemented using both 3 He and 129 Xe in multi‐site trials, 54,55 with notable HP 129 Xe multisite studies that included evaluation of CF 16 and asthma patients, 22 as well as recent phase III clinical trials of patients being evaluated for resection and transplant 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperpolarized (HP) 129 Xe gas magnetic resonance imaging (MRI) has been regarded as a powerful and noninvasive pulmonary imaging modality due to its ability to quantify regional ventilation, 1–4 microstructure, and gas exchange function of the lungs 5–8 . The potential of this technique in pulmonary disease diagnosis and evaluation has been demonstrated in previous studies 9–16 .…”
Section: Introductionmentioning
confidence: 99%